Legal Review of the Process of Handling Cases of Sexual Violence Against Children - Utama, Bobby Edwan Ramnissa; Hidayati, Rahmatul; Parmono, Budi (Borong Newinera Publisher, 2025)
This study aims to examine and analyze the handling of cases of sexual violence against children from a positive legal perspective, focusing on the implementation of legal procedures at the Batu Police Department. The method used is normative juridical, with a statutory and conceptual approach. The primary data sources consist of primary legal materials, such as the Criminal Code (KUHP), Law Number 35 of 2014 concerning Child Protection, Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, and Law Number 11 of 2012 concerning the juvenile criminal justice system. Secondary legal materials were obtained from academic literature, scientific journals, and relevant law enforcement documents. The results of the study indicate that normatively, the handling of cases of sexual violence against children is clearly regulated through laws and regulations that require maximum protection for child victims, including in investigations, special treatment during examinations, and the fulfillment of victims' rights. However, in practice at the Batu Police Department, law enforcement still faces various challenges, such as limited investigative resources, minimal psychological support, and a lack of understanding of the victim's perspective. Furthermore, the legal process still does not fully comply with the principles of restorative justice mandated by the latest regulations. This study recommends improving the capacity of investigators through gender-sensitive and child protection training, strengthening synergy between the police, child protection agencies, and supporting agencies, and ensuring ongoing oversight of the case handling process to ensure optimal protection of child victims' rights at every stage of the legal process.